Improving the ground service quality of Vietnam Airlines at Noibai international airport = Nâng cao chất lượng phục vụ mặt đất của Vietnam Airlines tại sân bay quốc tế Nội Bài - Nguyễn, Thị Tuyết (2020)
Aims of research: Determining the theoretical framework for the ground service quality and developing a scale for assessing the ground service quality provided by the airlines at the airport. Analysing the status of ground service quality of Vietnam Airlines at Noibai International Airport, on the basis of which finding the strengths, weaknesses and causes of weaknesses of this service quality. Proposing some solutions to improve the ground service quality of Vietnam Airlines at Noibai international airport